Creating Deaf-Friendly Spaces for Research: Innovating Online Qualitative Enquiries. - Ferndale, Danielle; Watson, Bernadette; Munro, Louise (Qualitative Research in Psychology)
In this article, we provide a reflexive account of the first author’s experience of designing and using an inclusive online forum to conduct research with people living in Australia with deafness or hearing loss. We reflect on the personal, institutional, pragmatic, and ontological influences on the project and how we managed these influences when they conflicted. In recounting this experience, we highlight the productive and restrictive aspects of doing research with deaf Australians in a university context and online. In addition to being a financially and time-effective method, the use of an online forum facilitated the recruitment of a geographically diverse sample of participants and enabled us to accommodate a range of linguistic preferences. However, as English is the dominant language in a Western context, analysing and publishing visual spatial languages in academia remains problematic, particularly in relation to the availability of expertise and issues regarding protecting anonymity.